Penerapan Audio Visual dalam Peningkatan Pemahaman Siswa pada Pembelajaran Gerakan Sholat Kelas IV Sekolah Dasar Negeri 1 Pengempon Kecamatan Sruweng - Yuli Ernawati; Laeli Mubarokah; Nur Farida Fatma; Siti Fatimah; Oky Ristya Trisnawati (IAINU Kebumen, 2023)
The purpose of this study is to apply audio-visual media to improve theskills of carrying out fardhu prayer movements for fourth grade students of SD Negeri 1 Pengempon and to find out learning outcomes can improve skills to carry out fardhuprayer movements by applying Audio Visual Media to fourth grade students of SD Negeri 1 Pengempon which affect it. The data collection technique is observation, namely direct observationof students who are practicing prayer and interviews, namely conducting direct questions and answers with Islamic Religious Education teachers at SD Negeri 1 Pengempon. Based on the results of the research that has been carried out, it canbeconcluded that the ability to practice fardhu prayers at SD Negeri 1 Pengempon is classified as capable based on the results of observations. The results that affect theability of students to practice fardhu prayers include the factors of supervisionandguidance carried out by PAI teachers in the practice of praying for children at school. As well as the results of complete prayer facilities provided by parents and the school and the results of coaching and supervision carried out by parents at home.